Remarks on Fenchel-Moreau conjugate in the setting of consumer theory - George H.M. Cunha; Michel A.C. Oliveira; Michel A.C. Oliveira; Wilfredo Sosa (EconomiA, 2016)
In this manuscript we consider the conjugate notion focused from consumer theory as an interesting tool. According to us, conjugate notion remained undeveloped in economic theory because Fenchel's conjugate notion was introduced exclusively for proper convex lower semi continuous functions and convexity assumption is not natural in economic theory. Nevertheless, we introduce necessary and sufficient optimality conditions for consumer problem. Also, we consider a particular version of Fenchel–Moreau conjugate notion, for lower semi continuous functions recently introduced in the literature as a generalization of Fenchel's conjugate. Finally, we adapt it to closed functions in order to define a convex dual problem for consumer problem. – – Neste artigo consideramos a noç\~ao de conjugada focalizada na teoria do consumidor como uma ferramenta interessante. Segundo nosso entendimento, a noç\~ao de conjugada ainda n\~ao foi desenvolvida na teoria econômica, porque a Conjugada de Fenchel foi introduzida exclusivamente para funç\~oes próprias, convexas semi continuas inferiormente e a convexidade n\~ao é uma hipóteses natural na teoria econômica. Mesmo assim, introduzimos condiç\~oes necessárias e suficientes de otimalidade para o problema do consumidor. Finalmente, considerando uma vers\~ao particular da Conjugada de Fenchel-Moreau para funç\~oes semi continuas inferiores, recentemente introduzida na literatura como uma generalizaç\~ao da conjugada de Fenchel, e à adaptamos para as funç\~oes fechadas com o objetivo de definir um problema dual convexo para o problema do consumidor.
Keywords: C02; C61; D11; 330; Convex analysis; Fenchel's conjugate; Economic theory